Menari Bersama Marya - I Komang Tri Ray Dewantara; Ni Wayan Suartini (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2025)
ABSTRACT “MENARI BERSAMA MARYA” I Komang Tri Ray Dewantara mangtriray@gmail.com This article discusses the creation of a dance work based on research through an archival dance approach titled